High-affinity binding sites for histone H1 in plasmid DNA. - Yaneva, J (1995)
The interaction of histone H1 isolated from chicken erythrocytes with restriction fragments from plasmids pBR322 and pUC19 was studied by gel electrophoresis. Certain restriction fragments exhibited unusually high affinity for the histone, forming high molecular mass complexes at protein to DNA ratios at which the other fragments did not show evidence for binding. The highly preferred fragments are intrinsically curved, as judged by their electrophoretic mobility in polyacrylamide gels, by computer modeling, and by imaging with scanning force microscopy. However, control experiments with either curved portions of the same fragments or highly curved kinetoplast DNA fragments showed that the presence of curvature alone was not sufficient for preferential binding. By using various restriction fragments centered around the highly preferred sequence, it was found that the high-affinity binding required in addition the presence of specific sequences on both sides of the region of curvature. Thus, both curvature and the presence of specific sites seem to be required to generate high affinity.